Bone Loss Triggered by the Cytokine Network in Inflammatory Autoimmune Diseases - Dulshara Sachini Amarasekara; Jiyeon Yu; Jaerang Rho (Journal of Immunology Research)
Bone remodeling is a lifelong process in vertebrates that relies on the correct balance between bone resorption by osteoclasts and bone formation by osteoblasts. Bone loss and fracture risk are implicated in inflammatory autoimmune diseases such as rheumatoid arthritis, ankylosing spondylitis, inflammatory bowel disease, and systemic lupus erythematosus. The network of inflammatory cytokines produced during chronic inflammation induces an uncoupling of bone formation and resorption, resulting in significant bone loss in patients with inflammatory autoimmune diseases. Here, we review and discuss the involvement of the inflammatory cytokine network in the pathophysiological aspects and the therapeutic advances in inflammatory autoimmune diseases.